Design of an IVA test mannequin model as a learning media for midwifery students at the Tasikmalaya Health Polytechnic, ministry of health - Nunung Mulyani; Herni Kurnia; Laila Putri Suptiani (Science Midwifery, 2026)
Introduction: Cervical cancer remains one of the leading causes of cancer-related deaths among women in Indonesia, particularly in developing countries. The Visual Inspection with Acetic Acid (IVA Test) is a simple, affordable, and sensitive method recommended by the World Health Organization (WHO) for early detection. However, many healthcare workers, including midwives, still lack sufficient skills in performing the test. This study aims to develop a prototype of an IVA Test manikin as an innovative learning medium to enhance midwifery students’ competencies. Methods: This research employed the Research and Development (R&D) approach through stages including anatomical graphic design of the cervix, prototype fabrication using medical-grade silicone, and simulation of acetic acid application using hypochlorite acid. The cervical part was designed modularly with litmus paper that turns white when applied with hypochlorite, mimicking a positive IVA reaction. Validation and consultation were conducted with material and media experts to assess design accuracy and functionality. A small-scale trial was carried out involving 10 midwifery students from Poltekkes Kemenkes Tasikmalaya. Results: The prototype successfully resembled the realistic shape, color, and texture of the cervix. Expert validation indicated that the manikin met anatomical and functional criteria, while student trials demonstrated that the model was easy to use, improved understanding of procedural steps, and increased confidence in performing the IVA Test. Conclusion: The developed IVA Test manikin serves as an effective, practical, and sustainable learning innovation to enhance midwifery students’ clinical skills in cervical cancer early detection. Further studies with larger samples and expert validation are recommended to optimize its educational model/video.